Afforestation on agricultural land in England: Applying the Theoretical Domains Framework and Behaviour Change Wheel to identify the enablers of change within farmer behaviour - J. Urquhart; A. Goodenough; P.L. Staddon; J. Mills; J. Powell; M. Vigani; P. Simmonds (Journal of Rural Studies, 2025)

Genomic analysis of Vanessa tameamea, the threatened Hawaiian endemic butterfly, reveals population genetic structure relevant to conservation efforts - Haley E. Arnold; Julian R. Dupuis; Daniel Rubinoff; William P. Haines; Michael San Jose; Renee L. Corpuz; Angela N. Kauwe; Tyler J. Simmonds; Scott M. Geib; Sheina B. Sim (Conservation Genetics, 2025)
Patterns of divergence and speciation on islands have long been of interest in the broader study of evolution. Hawaiʻi’s endemic Kamehameha butterfly ( Vanessa tameamea ) is experiencing population decline, but because of its high vagility and assumed genetic homogeneity as a species, its population structure has not been investigated. To evaluate V. tameamea genetic variation across the Hawaiian Islands, we assembled a reference quality genome assembly for the species using HiFi and HiC reads and performed range-wide population genetic analyses using ddRAD sequencing data. A discriminant analysis of principal components (DAPC) revealed that, contrary to prior assumptions, V. tameamea populations appear to be diverging based on geography, in a pattern similar to other native Hawaiian terrestrial arthropods. Specifically, through demographic history analyses, we find that the distinct population on Kauaʻi is likely to be ancestral, the central islands of Maui, Molokaʻi, and Oʻahu comprise another population, and Hawaiʻi Island forms a third population, with likely more gene exchange with the central islands. Finally, we investigate the SNPs driving differences between groups and find that many are associated with genes that may be relevant to local adaptation to environmental chemicals such as host plant defenses or chemicals introduced by human activity, notably to do with metabolism and detoxification. While much field work remains to investigate any cryptic or phenotypic patterns as well as quantify effective migration, we hope that this work will inform refinement of conservation plans for one of Hawaiʻi’s two native butterflies.

Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

Out of habitat marine mammals – Identification, causes, and management recommendations - Laetitia Nunny; Mike Bossley; Rebecca M. Boys; Philippa Brakes; Tilen Genov; E.C.M. Parsons; Katharina J. Peters; Naomi A. Rose; Claire A. Simeone; Karen A. Stockin; Courtney S. Vail; Krista van der Linde; et al. (Marine Policy, 2025)

Wilderness forms and their implications for global environmental policy and conservation - Katharina‐Victoria Pérez‐Hämmerle; Katie Moon; Rubén Venegas‐Li; Sean Maxwell; Jeremy S. Simmonds; Oscar Venter; Stephen T. Garnett; Hugh P. Possingham; James E. M. Watson (Conservation Biology, 2022)
With the intention of securing industry‐free land and seascapes, protecting wilderness entered international policy as a formal target for the first time in the zero draft of the Post‐2020 Global Biodiversity Framework under the Convention on Biological Diversity. Given this increased prominence in international policy, it is timely to consider the extent to which the construct of wilderness supports global conservation objectives. We evaluated the construct by overlaying recently updated cumulative human pressure maps that offer a global‐scale delineation of industry‐free land as wilderness with maps of carbon stock, species richness, and ground travel time from urban centers. Wilderness areas took variable forms in relation to carbon stock, species richness, and proximity to urban centers, where 10% of wilderness areas represented high carbon and species richness, 20% low carbon and species richness, and 3% high levels of remoteness (>48 h), carbon, and species richness. Approximately 35% of all remaining wilderness in 2013 was accessible in

Communicating the true challenges of saving species: response to Wiedenfeld et al. - James E. M. Watson; Jeremy S. Simmonds; Michelle Ward; Chuan J. Yong; April E. Reside; Hugh P. Possingham; Andrew Rogers; Josie Carwardine (Conservation Biology, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Correction to: Recommendations for the nomenclature of enteroviruses and rhinoviruses - P. Simmonds; A. E. Gorbalenya; H. Harvala; T. Hovi; N. J. Knowles; A. M. Lindberg; M. S. Oberste; A. C. Palmenberg; G. Reuter; T. Skern; C. Tapparel; K. C. Wolthers; et al. (Archives of Virology, 2020)
Unfortunately, one of the affiliations of author “A. E. Gorbalenya” was missed in original version. The affiliation is updated here.

Recommendations for the nomenclature of enteroviruses and rhinoviruses - P. Simmonds; A. E. Gorbalenya; H. Harvala; T. Hovi; N. J. Knowles; A. M. Lindberg; M. S. Oberste; A. C. Palmenberg; G. Reuter; T. Skern; C. Tapparel; K. C. Wolthers; et al. (Archives of Virology, 2020)
Enteroviruses (EVs) and rhinoviruses (RVs) are significant pathogens of humans and are the subject of intensive clinical and epidemiological research and public health measures, notably in the eradication of poliovirus and in the investigation and control of emerging pathogenic EV types worldwide. EVs and RVs are highly diverse in their antigenic properties, tissue tropism, disease associations and evolutionary relationships, but the latter often conflict with previously developed biologically defined terms, such as “coxsackieviruses”, “polioviruses” and “echoviruses”, which were used before their genetic interrelationships were understood. This has created widespread formatting problems and inconsistencies in the nomenclature for EV and RV types and species in the literature and public databases. As members of the International Committee for Taxonomy of Viruses (ICTV) Picornaviridae Study Group, we describe the correct use of taxon names for these viruses and have produced a series of recommendations for the nomenclature of EV and RV types and their abbreviations. We believe their adoption will promote greater clarity and consistency in the terminology used in the scientific and medical literature. The recommendations will additionally provide a useful reference guide for journals, other publications and public databases seeking to use standardised terms for the growing multitude of enteroviruses and rhinoviruses described worldwide.

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Ratification vote on taxonomic proposals to the International Committee on Taxonomy of Viruses (2015) - M. J. Adams; E. J. Lefkowitz; A. M. Q. King; D. H. Bamford; M. Breitbart; A. J. Davison; S. A. Ghabrial; A. E. Gorbalenya; N. J. Knowles; P. Krell; R. Lavigne; D. Prangishvili; et al. (Archives of Virology, 2015)

Vertical characteristics of cyclonic tracks over the eastern Mediterranean during the cold period of the year - H. A. Flocas; P. Kountouris; J. Kouroutzoglou; M. Hatzaki; K. Keay; I. Simmonds (Theoretical and Applied Climatology, 2013)

Susceptibility to Fusarium head blight is associated with the Rht-D1b semi-dwarfing allele in wheat - Srinivasachary; N. Gosman; A. Steed; J. Simmonds; M. Leverington-Waite; Y. Wang; J. Snape; P. Nicholson (Theoretical and Applied Genetics, 2008)

Mapping of a gene (Vir) for a non-glaucous, viridescent phenotype in bread wheat derived from Triticum dicoccoides, and its association with yield variation - J. R. Simmonds; L. J. Fish; M. A. Leverington-Waite; Y. Wang; P. Howell; J. W. Snape (Euphytica, 2008)

Cytochrome f from the Antarctic psychrophile, Chlamydomonas raudensis UWO 241: structure, sequence, and complementation in the mesophile, Chlamydomonas reinhardtii - Loreta Gudynaite-Savitch; Michael Gretes; Rachael M. Morgan-Kiss; Leonid V. Savitch; John Simmonds; Susanne E. Kohalmi; Norman P. A. Hüner (Molecular Genetics and Genomics, 2006)

AGAGE Observations of Methyl Bromide and Methyl Chloride at Mace Head, Ireland, and Cape Grim, Tasmania, 1998–2001 - P. G. Simmonds; R. G. Derwent; A. J. Manning; P. J. Fraser; P. B. Krummel; S. O'Doherty; R. G. Prinn; D. M. Cunnold; B. R. Miller; H. J. Wang; D. B. Ryall; L. W. Porter; et al. (Journal of Atmospheric Chemistry, 2004)

Effect of Botanical Insecticides on the Foraging and Feeding Behavior of the Coccinellid PredatorCryptolaemus montrouzieri - M. S. J. Simmonds; J. D. Manlove; W. M. Blaney; B. P. S. Khambay (Phytoparasitica, 2000)

Hydroxyl Radical Concentrations Estimated from Measurements of Trichloroethylene during the EASE/ACSOE Campaign at Mace Head, Ireland during July 1996 - R. G. Derwent; N. Carslaw; P. G. Simmonds; M. Bassford; S. O'Doherty; D. B. Ryall; M. J. Pilling; A. C. Lewis; J. B. McQuaid (Journal of Atmospheric Chemistry, 1999)

Classification, nomenclature, and database development for hepatitis C virus (HCV) and related viruses: proposals for standardization - B. Robertson; G. Myers; C. Howard; T. Brettin; J. Bukh; B. Gaschen; T. Gojobori; G. Maertens; M. Mizokami; O. Nainan; S. Netesov; K. Nishioka; et al. (Archives of Virology, 1998)

Methyl Sulphone Metabolites of Polychlorinated Biphenyls (PCBs) in Cetaceans from the Irish and the Aegean Seas - G. M. Troisi; K. Haraguchi; M. P. Simmonds; C. F. Mason (Archives of Environmental Contamination and Toxicology, 1998)

Photooxidation of Nimbin and Salannin, Tetranortriterpenoids from the Neem Tree (Azadirachta indica) - Andrew P. Jarvis; Shaun Johnson; E. David Morgan; Monique S. J. Simmonds; Wally M. Blaney (Journal of Chemical Ecology, 1997)

On the Spatial Distribution and Seasonal Variation of Lower-Troposphere Ozone over Europe - H. E. Scheel; H. Areskoug; H. Geiss; B. Gomiscek; K. Granby; L. Haszpra; L. Klasinc; D. Kley; T. Laurila; A. Lindskog; M. Roemer; R. Schmitt; et al. (Journal of Atmospheric Chemistry, 1997)